Wednesday, 21 September 2016

Find the inference rule of the given functional dependency

Find the inference rule of the given functional dependency / Armstrong's axioms / Inference rules / Normalization process


1. For a relation R(A, B, C), if A → B and A → C holds, then A → BC also holds. Which of the following rule ensures this?

(a) Augmentation rule
(b) Union rule
(c) Decomposition rule
(d) None of the above


(b) Union rule

Union rule says that a set of functional dependencies that have same left hand side attributes can be combined to form a single functional dependency. For example, the FDs AC → B, AC → DE and AC → F can be combined to AC → BDEF.

Decomposition rule is the opposite of union rule. Augmentation rule is about adding same set of attributes on both sides of a functional dependency.

         Previous Question                                                                                Next Question

No comments:

Post a Comment

SQL exercises for beginners one

SQL Exercises for Beginners / Simple SQL Exercises with Answers / Solved SQL exercises / SQL solved exercises with simple conditions / So...